Stress-induced changes in nociceptive responding post-surgery in preclinical rodent models - Bella, Ariadni; Diego, Alba M.; Finn, David P.; Roche, Michelle (Frontiers in Pain Research, 2023)
Chronic post-surgical pain affects up to 85% of individuals depending on the type of surgery, the extent of inflammation, tissue and/or nerve damage. Pre-surgical stress is associated with greater pain intensity, prolonged recovery and is one of the main risk factors for the development of chronic post-surgical pain. Clinically valid animal models provide an important means of examining the mechanisms underlying the effects of stress on post-surgical pain and identifying potential novel therapeutic targets. This mini-review discusses the current data from preclinical animal studies examining the effect of stress on post-surgical pain, the potential underlying mechanisms and gaps in the knowledge that require further investigation.